Augmented dan Virtual Reality sebagai Media Promosi Interaktif Museum Perumusan Naskah Proklamasi - Christopher Lourdes Palagiang; Sofiani Sofiani (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2021)
Augmented and Virtual Reality technology is a technology that continues to develop every year, especially in the world of tourism and can be used as an interactive promotional media. This study aims to see the use of Augmented and Virtual Reality technology as an Interactive Promotional Media with qualitative methods. The results showed that there is the utilization of Augmented Reality technology with the name of Digital Museum with the help of Siji application and also the use of Virtual Reality technology with the name of Online or Virtual Exhibition on the website of the Museum of Proclamation Manuscript Formulation as an interactive promotional media. The conclusion obtained from this research shows that Siji application can be a means of interactive promotional media and give a real impression while the Online Exhibition can provide information and knowledge about the Museum of Proclamation Manuscript Formulation. It is recommended to continue to utilize the technology that develops every year.